From Consumers to Communicators: Reimagining the Role of Youth in Agricultural Extension Communication- A Systematic Review - Joshi, Hem Raj; Devkota, Shishir; Chand, Purnesh (Journal of the Institute of Agriculture and Animal Science, 2025)
There is growing recognition for young people as proactive communicators and agents of change within the agricultural communication ecosystem. The transformative role of youth in agricultural extension communication is examined in this study, with particular attention paid to how they might use digital technologies and participatory ways to close the gap between traditional agricultural practices and contemporary advances. The research accesses the present contributions of youths, obstacles to their active involvement, and successful strategies to increase their engagement through a thorough literature analysis. The results highlight how youth-led communication promotes inclusivity and sustainability in agricultural extension programs while also hastening the adoption of innovations. In order to meet the problems of contemporary agriculture, young people may transform the agricultural extension landscape by acting as innovators, educators, and advocates by utilizing their adaptability and technological know-how. To empower youths as communicators in agricultural extension systems, the report ends by suggesting specific strategies as such integrating ICT, providing specialized training, and encouraging policy advocacy.